Studying cultures - Ochoa, Anna-; Cherryholmes, Cleo H; Manson, Gary (McGraw-Hill : New York Webster Division, 1979)
A fourth grade textbook which discusses four subcultures: the Tasaday of of the Philippines, the Mossi of Upper Volta, the Aymara of Bolivia, and the Uzbeks of the Soviet Union.
Includes index.
Keywords: Ethnology -- Juvenile literature